Pengelolaan Bank Sampah sebagai implementasi Ekonomi Kreatif di Bank Sampah Guyub Rukun Dusun Madugondo, Kecamatan Piyungan, Bantul: Waste Bank Management as an Implementation of the Creative Economy at Guyub Rukun Dusun Madugondo Waste Bank, Piyungan District, Bantul - Istanabi, Tendra; Miladan, Nur; Suminar, Lintang; Kusumastuti, Kusumastuti; Aliyah, Istijabatul; Soedwiwahjono, Soedwiwahjono; Utomo, Rizon Pamardhi; Werdiningtyas, Rr. Ratri; Yudana, Galing (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
One of the concrete steps of waste management that can be felt directly by the community in a small scope is the Waste Bank. However, the community often faces problems in managing waste through waste banks, namely related to limited human resources and facilities. The Guyub Rukun Dusun Madugondo waste e Bank is a waste bank that is experiencing problems with limited human resources and facilities. Efforts are needed to overcome the limitations of human resources and facilities so that the waste bank is able to continue to grow. Therefore, this community service activity is carried out to help overcome these problems by providing training methods to improve the managerial skills of waste bank managers and innovation in processing waste into creative economic products as well as providing supporting facilities grants. The training was carried out with waste bank management materials and making flower arrangements from recycled plastic waste materials. Meanwhile, the grant for supporting facilities is realized in the form of a waste press. The results of these community service activities can be felt directly by the waste bank manager and can reduce the problems faced by the Guyub Rukun Dusun Madugondo waste Bank manager.